Voice of the turtle: The underwater acoustic repertoire of the long-necked freshwater turtle, Chelodina oblonga - Giles, J.; Davis, J.; McCauley, Robert; Kuchling, G. (Acoustical Society of America, 2009)
Chelodina oblonga is a long-necked, freshwater turtle found predominantly in the wetlands on the Swan Coastal Plain of Western Australia. Turtles from three populations were recorded in artificial environments set up to simulate small wetlands. Recordings were undertaken from dawn to midnight. A vocal repertoire of 17 categories was described for these animals with calls consisting of both complex and percussive spectral structures. Vocalizations included clacks, clicks, squawks, hoots, short chirps, high short chirps, medium chirps, long chirps, high calls, cries or wails, hooos, grunts, growls, blow bursts, staccatos, a wild howl, and drum rolling. Also, a sustained vocalization was recorded during the breeding months, consisting of pulse sequences that finished rhythmically. This was hypothesized to function as an acoustic advertisement display. Chelodina oblonga often lives in environments where visibility is restricted due to habitat complexity or poor light transmission due to tannin-staining or turbidity. Thus the use of sound by turtles may be an important communication medium over distances beyond their visual range. This study reports the first records of an underwater acoustic repertoire in an aquatic chelonian.